PENGARUH STRATEGI PEMILIHAN PELAYANAN TERHADAP KEPERCAYAAN DAN KEPUASAN PELANGGAN - Jatmiko, Robby; Sugiharti, Sugiharti (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2018)
Despite having been widely studied in traditional services, the effectof service recovery (SFR) on customer loyalty has received only limitedattention. This paper sets out to empirically test the following set ofhypotheses in an flight service. The paper is based on The paper is basedon online survey of actual customers of a flight service. This articleargues that perceptions of justice (distributive, procedural, andinteractional justice) in service recovery influence customer trust &satisfaction towards the service firm, which in turn affects customerloyalty. Customers’ trust and satisfaction in service providers wereproposed to mediate the relationship between perceived justice to servicerecovery efforts and subsequent loyalty intention.